Management of Infrastructure in Madrasah Educational Institutions - Amarullah, Mohammad Syarifuddin; Miftahudin, Miftahudin; Uyuni, Yuyun Rohmatul; Bachtiar, Machdum (Formosa Journal of Science and Technology, 2024)
The aim of this research is to determine the management or management of advice and infrastructure in madrasah or school educational institutions. The research method used is the research method used in this writing literature study which focuses on searching for sources through books, journals, and available literature. The results of this writing are (1) planning of facilities and infrastructure in educational institutions including design or purchase planning, procurement of facilities and infrastructure, and equipment distribution planning; (2) organization of facilities and infrastructure including (a) grouping of facilities and infrastructure (b) room arrangement; (3) implementation includes the procurement and utilization of facilities and infrastructure contained in educational institutions so that the use of infrastructure to support activities or teaching-learning processes can run effectively and efficiently; (4) evaluation of facilities and infrastructure in educational institutions is carried out continuously and re-planned, namely by looking at how effective and efficient the facilities and infrastructure in educational institutions are so that in the future, better improvements can be made because the facilities become a factor in the continuity of learning activities.